Student Motivation to Participate in Corner Learning for Class X BDP 1 and 2 Students at SMK Negeri 9 Samarinda - Armain, Armain (Educationist: Journal of Educational and Cultural Studies, 2022)
This research aims to determine the motivation of students to take part in PJOK learning at SMK Negeri 9 Samarinda. This research is a quantitative descriptive research with a survey method. The data collection technique in this research uses a questionnaire instrument. The population in this study were all class X BDP 1 dan 2 students at SMK Negeri 9 Samarinda using purposive sampling, with a total of 60 students. Data analysis uses descriptive analysis with percentages. Based on the overall research results of 60 students, of which in the "very high" category there were 4 students (6.66%), in the "high" category there were 19 students (31.66%), in the "medium" category there were 16 participants. students (26.66%), the "low" category was 18 students (30%), and the "very low" category was 3 students (5%). It was concluded that the motivation of students to take PJOK at SMK Negeri 9 Samarinda with an average of 63.73 was in the medium category.